Ministry of Public Business Sector Decree No. 29 of the Year 2016 With Regard to the Controls of Representing the Public Money in the Joint Ventures in which the Holding Companies and Subsidiaries subject to the Ministry of Public Business Sector Have Shareholdings = وزارة قطاع الأعمال العام قرار رقم 29 لسنة 2016 بشأن ضوابط تمثيل المال العام بالشركات المشتركة التى تساهم فيها الشركات القابضة والتابعة الخاضعة لوزارة قطاع الأعمال العام - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic